644. Borrelia miyamotoi and Borrelia burgdorferi Seroprevalence in New England. (31st December 2020) - Johnston, Demerise; Kelly, Jill; Ledizet, Michel; Lavoie, Nathalie; Krause, Peter J
Abstract: Background: Diseases vectored by the tick species Ixodes scapularis have increased in incidence over the past 50 years and have been expanding into previously non-endemic areas. The emergence of Borrelia miyamotoi, a recently described spirochetal pathogen, has been less well documented than that of Borrelia burgdorferi, the causative agent of Lyme disease. The objective of this study was to compare the geographic range of human exposure to B. miyamotoi and B. burgdorferi in New England, the pattern of their spatial expansion, and factors that influence their frequency. Methods: Serum samples were collected from 11 study sites across New England. Age, gender, race, and residential zip code or county were recorded for each study participant and aggregate data analyzed by study sites, study site zones, and residential county for spatial analysis. Serum samples were tested for B. miyamotoi antibody using a multiplex Luminex assay and for B. burgdorferi antibody using a recently FDA approved two-tiered ELISA (Zeus ELISA Test Systems). Fischer exact tests and map visualizations in ArcGIS Pro 2.4.2 (Copyright ©2019 Esri Inc.) were used to determine spatial distribution of human B. miyamotoi and B. burgdorferi infection in New England. A logistic regression model was used to determine any association in seropositivity with tick-borne infection risk factors. Results: B. burgdorferi seroprevalence was greater than that of B. miyamotoi at all but one study site. The average B. burgdorferi seroprevalence at all study sites was not quite double that of B. miyamotoi (mean 2.3% [0.6-6.2%] and mean 4.1% [2.2-7.5%], respectively). No longitudinal or latitudinal gradient was observed for B. miyamotoi or B. burgdorferi seroprevalence by study site zone or county analysis. Men were twice as likely as women to be seropositive for B. miyamotoi and B. burgdorferi . Conclusion: Human exposure to B. miyamotoi and B. burgdorferi is highly dispersed throughout New England. B. miyamotoi seroprevalence is about half that of B. burgdorferi in New England. Additional studies are needed to explain the disparity between B. burgdorferi and B. miyamotoi infection and disease. Disclosures: All Authors : No reported disclosures